Assessing the strategic alignment maturity in a Malaysian public sector agency: a case study of Malaysian Administrative Modernisation and Management Planning Unit - Jamali A.S.; Sulaiman H.; Dhillon J.S. (Inderscience Publishers, 2023)
Public administration; Alignment dimension; Alignment sub-dimension; Malaysian administrative modernization and management planning unit; Malaysian public sectors; Malaysians; Management planning; Maturity model; Modernization and management planning unit; Planning units; Strategic alignment; Strategic alignment maturity model; Alignment